Inspiratory muscle training in patients with obesity: a systematic review and meta-analysis - Caicedo-Trujillo, Saúl; Torres-Castro, Rodrigo; Vasconcello-Castillo, Luis; Solis-Navarro, Lilian; Sanchez-Ramirez, Diana; Núñez-Cortés, Rodrigo; Vera-Uribe, Roberto; Muñoz-Muñoz, Isabel; Barros-Poblete, Marisol; Romero, Juan Eduardo; Vilaró, Jordi (Frontiers in Medicine, 2023)
Introduction Obesity is a chronic medical condition that affects, among others, the cardiovascular and respiratory systems. Interventions for its treatment focus on sustained weight reduction and general health improvement, leaving respiratory management aside. Our objective was to determine the effects of inspiratory muscle training (IMT) in patients with obesity. Methods A systematic review was performed in Embase, Cochrane Library (CENTRAL), CINAHL, Web of Science, and PubMed/MEDLINE on June 26, 2023. Randomized clinical trials (RCTs), and quasi-randomized clinical trials investigating the effects of IMT in people with obesity were included. Selected studies were screened by two independent reviewers who extracted data and assessed the quality of the evidence. Results The initial search returned 705 potential studies were included. Ultimately, eight studies met the criteria for eligibility and were included in the review. IMT improves physical capacity [6-minute walk test (6MWT): 44.5 m, 95% CI: 30.5 to 58.5; p < 0.0001] and the strength of the inspiratory muscles [maximal inspiratory pressure (MIP): −28.4 cm H2O, 95% CI: −41.9 to −14.8; p < 0.0001] compared to the controls, without differences in the pulmonary function, body mass index (BMI) and metabolic parameters. Conclusion Inspiratory muscle training improves physical capacity and inspiratory muscle strength without significant changes in lung function, BMI, and metabolic parameters. Systematic review registration: PROSPERO, identifier CRD42023439625, https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023439625.